Ethnopharmacological Survey among Traditional Medicine Practitioners in Abidjan (Côte d’Ivoire) for the Management of Pathologies such as Malaria, ENT Diseases, Diarrhea, Typhoid Fever and Anemia - E. Kroa; C. A. F. Anderson; B. Yao Kouamé; M. P. Kouadio Yobouet (New Horizons in Medicine and Medical Research Vol. 8, 2022)
The medicinal plants are known to the Traditional Medicine Practitioners (TMPs) of Côte d’Ivoire. Several studies and scientific research have proved the effectiveness of medicinal plants used in the management of common pathologies, such as malaria (KROA, 2004), diabetes (N’GUESSAN et al, 2013). The current policy is to integrate traditional medicine and pharmacopeia into the national health system in order to improve the health coverage of the health needs of populations, in particular in the management of commonly encountered diseases such as malaria, ENT diseases, diarrhea, typhoid fever and anemia in the Abidjan District by PMT. The aim of this study is to promote the use of traditional medicine and pharmacopeia in the national health system. This study was conducted with fifty (50) PMTs in the District of Abidjan over a three-month period. At the end of this study, 30 out of 50 of the PMTs surveyed, or 60%, were plant therapists. 61 species of medicinal plants belonging to 36 families are used in traditional medicine centers against five pathologies. Thirty-four (34) plant species are used for malaria, nineteen (19) for ENT diseases, fourteen (14) for diarrhea, seventeen (17) for typhoid fever and fourteen (14) for anemia. The most commonly used plant parts are leaves and bark in the form of decoctions, infusions and macerations for oral or dermal administration. Medications used by PMTs are essentially herbal substances. This therapeutic arsenal explains the important place that the Ivorian pharmacopeia occupies in the management of the health problems of the populations. The pharmacological effects reported in this study are consistent with the literature. However, this rich potential of herbal medicine requires further investigation of the properties of these plants in order to improve their use. This study assessed the importance of medicinal plants in addressing population health problems. The contribution of PMTs is essential in the process of producing improved traditional medicines. These species are potential resources that may lead to the isolation of phytocompounds of therapeutic interest whose efficacy and safety are guaranteed by scientific studies.